From isoniazid to psychobiotics: the gut microbiome as a new antidepressant target. (2nd March 2019) - Butler, Mary I; Sandhu, Kiran; Cryan, John F; Dinan, Timothy G
Abstract : An awareness of the importance of the gut–brain axis in psychiatric disorders such as depression is increasing. The gut microbiome is a key component of this axis. Gut bacteria can communicate with the brain through a variety of pathways including the hypothalamic–pituitary–adrenal axis, immune modulation, tryptophan metabolism and the production of various neuroactive compounds. Patients with depression, and other mood and anxiety disorders, show distinct compositional changes in their gut bacteria profile, raising the question about a possible aetiological role for the microbiome in these disorders. Evidence is emerging that the gut microbiome may represent a new potential antidepressant target and the term 'psychobiotic' has been coined to describe bacteria which confer mental health benefits. Gut bacteria are easily accessible and can be altered in a variety of ways including through the use of probiotics, prebiotics and dietary change. Psychobiotics containing various Lactobacillus and Bifidobacterium species have demonstrated the ability to improve mood, reduce anxiety and enhance cognitive function in both healthy populations and patient groups. This article provides an overview of the identification and development of antidepressant psychobiotics, from the preclinical evidence in the laboratory to the more recent encouraging results from human trials.